SMARCAL1, the annealing helicase and the transcriptional co‐regulator. Issue 10 (5th August 2020) - Bansal, Ritu; Hussain, Saddam; Chanana, Upasana Bedi; Bisht, Deepa; Goel, Isha; Muthuswami, Rohini
Abstract: The ATP‐dependent chromatin remodeling proteins play an important role in DNA repair. The energy released by ATP hydrolysis is used for myriad functions ranging from nucleosome repositioning and nucleosome eviction to histone variant exchange. In addition, the distant member of the family, SMARCAL1, uses the energy to reanneal stalled replication forks in response to DNA damage. Biophysical studies have shown that this protein has the unique ability to recognize and bind specifically to DNA structures possessing double‐strand to single‐strand transition regions. Mutations in SMARCAL1 have been linked to Schimke immuno‐osseous dysplasia, an autosomal recessive disorder that exhibits variable penetrance and expressivity. It has long been hypothesized that the variable expressivity and pleiotropic phenotypes observed in the patients might be due to the ability of SMARCAL1 to co‐regulate the expression of a subset of genes within the genome. Recently, the role of SMARCAL1 in regulating transcription has been delineated. In this review, we discuss the biophysical and functional properties of the protein that help it to transcriptionally co‐regulate DNA damage response as well as to bind to the stalled replication fork and stabilize it, thus ensuring genomic stability. We also discuss the role of SMARCAL1 in cancer and the possibility of using this protein as a chemotherapeutic target.